Coaching athletes on the path to expertise: strategies to foster conscientiousness, grit, and self-control - Tedesqui, R. A. B.; Young, B. W. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
Conscientiousness, grit, and self-control are athlete personality characteristics that have been shown to differentially predict criteria of expertise development, including deliberate practice and higher skill levels (Tedesqui & Young, 2018; Toering & Jordet, 2015). Little is known about coaches` views on (a) whether these conscientiousness-related traits are more stable/malleable, (b) strategies that can help athletes develop these traits, or (c) whether coaches consider these traits when making talent identification and development (TID) decisions. To fill these gaps, semi-structured interviews were conducted with 11 high-performance coaches (9 male, 2 female), representing individual (5) and team sports (6), at national and international competitive levels. Data were analyzed using inductive thematic analysis (Braun & Clarke, 2006). Although coaches viewed these traits as mostly stable, they also considered them amenable to development. To help athletes develop grit/perseverance, coaches exposed athletes to failures and created challenging training conditions. Other strategies to foster conscientiousness-related traits included building good training habits and having honest one-on-one conversations about athletes` behaviours. Prompted through a hypothetical scenario, coaches generally preferred to work with less talented athletes who displayed high levels of the investigated traits as opposed to talented athletes with lower trait levels; a high level of both trait and talent was identified as ideal. Coaches revealed not measuring but intuitively considering conscientiousness-related traits in their TID decisions, especially in the context of athlete development, but to a lesser extent at the highest competitive levels where winning took primacy. Results have implications for coaching and the development of desirable traits.